“Pacific’s Ancestral Sounds”: Didactic sequence for promoting Colombian pacific wisdom through the development of english oral production in Eighth-Grade students (2022)
In a bilingual educational system which sets aside the learner's culture and traditions, it is imperative to develop pluricultural competencies in language learning that allow the learners to create a relationship with their surrounding context. The present design of a didactic sequence is focused on Colombian Pacific Ancestral Wisdom for oral production in L2 in order to improve English skills and ethnic-related content development. It also intends to include sung narratives since it significantly encourages students’ creativity to make different worlds through songs based on cultural stories. Therefore, this proposal was developed for eighth-grade students of a public school of Pereira, and based on the Colombian afro-descendant community.